Implementing Anticorruption Programs in the Private Sector - Berenbeim, Ronald E.; Arvis, Jean-Francois (World Bank, Washington, DC, 2012)
Although attention has focused on public sector initiatives to fight corruption on the demand side, private companies in every region have developed programs to fight it on the supply side. Policymakers and advocacy groups-such as Transparency International-consider such preventive efforts to be a critical component of the anticorruption toolkit. All types of firms-large and small, multinational and local-recognize that corruption raises the cost of doing business and should be prevented. Most company anticorruption programs rely on compliance systems that consist of a company code of conduct, training, and decisionmaking and reporting mechanisms. This self regulatory approach was pioneered in the 1970s by U.S. multinational corporations after unethical practices were revealed and in response to the 1977 Foreign Corrupt Practices Act. Until recently this approach was greeted with skepticism outside the United States. Critics argued that efforts to implement U.S. compliance-based techniques would fail in other business cultures. Skeptics also questioned the effectiveness of company anticorruption programs. But such views have changed considerably in recent years, and compliance systems are being implemented by companies from high-income countries as well as emerging markets. Moreover, anticorruption techniques have become more sophisticated in established U.S. systems.